Energy efficiency in buildings. (CIBSE, 2012)
This 3rd edition includes a new section on developing an energy strategy. It incorporates new and revised guidance published since 2004, including key CIBSE documents and publications by the Carbon Trust and BSRIA.
Keywords: Buildings -- Energy conservation.; elektronické knihy; electronic books